Dawn Of The Mobile Malware: Reviewing Mobile Worms . - Sarwar, Usman; Ramadass, Sureswaran; Budiarto, Rahmat (2007)
There is a new era of worm attack on mobile devices. In the past, worms on cell phones and PDA were more like science fiction but recently it is more than a reality. The objective of this paper is to brief the new threats on mobile devices and review the current hazards on it. We did taxonomy of current malware on mobile devices specifically worms and state their technical details.